Natural Zeolite Sample and Investigation Its Use in Oil Bleaching Sector - Bilgin, Öykü (WORLD MULTIDISCIPLINARY EARTH SCIENCES SYMPOSIUM (WMESS 2017), 2017)
In the sector of oil bleaching, the stored raw oil is subjected to physical and chemical methods such as degumming, neutralization, bleaching, deodorization and winterization. In the process of oil bleaching, the selection of correct bleaching earth in accordance with oil characteristics matters so much. Bleaching earth is an inorganic product used in removing impurities being available within the structures of vegetable, animal oil (sunflower, soya, corn, palm, tallow, rapeseed, fish oils. etc.) and fatty acids, mineral oils (glycerine, paraffin, mineral motor oils. etc.) with the adsorption process. The factors such as low cost of oil bleaching earth, low ratio of oil retaining, high bleaching capacity in spite of using them in small amounts, filter's delayed blocking by the earth and non-increase of the free acidity of the oil should be taken into consideration. Bleaching earths are processed with some acids in order to widen their surface areas. During this process, a certain amount of acid is left within oil bleaching earths even if it is very little. These acids also increase oil's acidity by oxidizing oil in the course of bleaching process. In this study, zeolite sample taken from Manisa -Demirci region was used. Following the processes of crushing and sieving, zeolite sample was subjected to chemical analyses according to their grain thickness, microscopic examination, the analyses of XRD and cation exchange capacity and their ore characteristics were determined. Afterwards, it was searched whether zeolite sample has oil bleaching ability or not or whether it can be used as oil bleaching earth or not.
Keywords: Natural Zeolite; Oil; Oil Sector